2021
DOI: 10.1096/fba.2020-00147
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte‐derived extracellular vesicles in health and diseases: Nano‐packages with vast biological properties

Abstract: As the largest human energy reservoir, adipocytes drive an intense dialog with other cells/organs throughout the body to regulate the size of adipose tissue and to communicate with other metabolic tissues and the brain to regulate energy supply. Adipokines have long been described as mediators of this crosstalk, participating in obesity‐associated complications. Recently, adipocyte‐derived extracellular vesicles (Ad‐EVs) have emerged as new key actors in this communication due to their powerful capacity to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 106 publications
0
11
0
Order By: Relevance
“…Interestingly, the treatment with metformin and pioglitazone, two compounds used for the management of metabolic syndrome, has been shown to increase the adiponectin/leptin ratio and improve the inflammatory profile, coinciding with decreased brain lesions in MS patients [ 51 ] and reduced cancer risk [ 52 ]. Adipocytes also release extracellular vesicles (EVs) that play a role in several pathophysiological conditions [ 53 ]. It is worth noting that EVs released by adipocytes stimulate fatty acid oxidation and migration in melanoma cells [ 54 ] and are involved in macrophage activation [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the treatment with metformin and pioglitazone, two compounds used for the management of metabolic syndrome, has been shown to increase the adiponectin/leptin ratio and improve the inflammatory profile, coinciding with decreased brain lesions in MS patients [ 51 ] and reduced cancer risk [ 52 ]. Adipocytes also release extracellular vesicles (EVs) that play a role in several pathophysiological conditions [ 53 ]. It is worth noting that EVs released by adipocytes stimulate fatty acid oxidation and migration in melanoma cells [ 54 ] and are involved in macrophage activation [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The biological cargos of EVs include proteins, nucleic acids, and lipids, which can be categorized into conventional and disease-related markers. ,, The conventional EV markers, which are proteins, are typically associated with the plasma membrane and cytosol, and are involved in lipid metabolism. Although how to differentiate between different types of EVs, especially MVs and exosomes, based on protein markers is still a matter of debate, it is expected that different EV subtypes exhibit distinct protein profiles due to the different biogenesis pathways. ,, Nonetheless, there is often considerable overlap in the protein profiles, largely attributed to the absence of standardized isolation and analysis methods for EVs. , …”
Section: Biomarkers For Evsmentioning
confidence: 99%
“…Many studies have reported that they have also been associated with physiopathological disorders related to obesity, such as oxidative stress, impaired adipogenesis, insulin signalling, angiogenesis, and inflammation [ 23 , 27–29 ]. Furthermore, some of them are secreted in vesicles and actively participate in intercellular communication [ 30–32 ]…”
Section: Introductionmentioning
confidence: 99%